1997
DOI: 10.1093/bja/79.5.662
|View full text |Cite
|
Sign up to set email alerts
|

Autotransfusion in major orthopaedic surgery: experience with 1785 patients

Abstract: Using a prospective audit, we have evaluated the efficacy of an integrated autotransfusion regimen which comprised predepositing and intra- and postoperative blood salvage in major orthopaedic surgery. We examined prospectively the records of 1785 patients (1198 females, 5867 males, mean age 62 (range 16-90) yr, preoperative haemoglobin concentration 13.4 (SD 1.4) g dl-1) undergoing total hip arthroplasty (THA, 1229 patients), THA after removal of internal fixation devices (RFD + THA, 18 patients), total knee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…The goal of this retrospective study was to analyze the efficacy of autologous transfusion in primary total knee and total hip arthroplasty (TKA, THA). Borghi et al stated that the risk for intravenous blood substitution rises with age and the ASA-Score and depends on gender, with a higher risk for transfusion in female patients [9]. In contrast, in the current study, blood loss was significantly higher in male patients.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The goal of this retrospective study was to analyze the efficacy of autologous transfusion in primary total knee and total hip arthroplasty (TKA, THA). Borghi et al stated that the risk for intravenous blood substitution rises with age and the ASA-Score and depends on gender, with a higher risk for transfusion in female patients [9]. In contrast, in the current study, blood loss was significantly higher in male patients.…”
Section: Discussioncontrasting
confidence: 76%
“…Focusing on the results in patients undergoing TKA, blood loss was neither influenced by the patient's BMI nor by the ASA score in the current cohort. Previous studies found ASA score to be a contributing factor towards the necessity for blood transfusion [9,14]. In the current patient cohort male TKA patients had significantly higher amounts of blood loss and allogenic transfusions.…”
Section: Discussionmentioning
confidence: 64%
“…Borghi et al. 37 used this combination of autotransfusion methods in a prospective series of 1785 patients undergoing primary or revision arthroplasty of the knee or hip, and only 7.3% of patients received allogeneic blood transfusions.…”
Section: Effectiveness Of Perioperative Red Cell Salvagementioning
confidence: 99%
“…Since 1990 a large database was recorded at our institution for quality control of an integrated auto-transfusion regimen, including information from nearly 3,000 patients undergoing major orthopedic surgery [5,6]. The database includes data on thromboembolic prophylaxis and symptomatic thromboembolic complications up to 30 days after surgery.…”
Section: Introductionmentioning
confidence: 99%